On the binomial edge ideals of block graphs - Chaudhry Faryal; Dokuyucu Ahmet; Irfan Rida (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica, 2016)
We find a class of block graphs whose binomial edge ideals have minimal regularity. As a consequence, we characterize the trees whose binomial edge ideals have minimal regularity. Also, we show that the binomial edge ideal of a block graph has the same depth as its initial ideal.